Analysis Of Basic Immunization Services With Mothers' Satisfaction In Puskesmas Care See Pokhisen - Martaulina Sinaga (Science Midwifery, 2021)
Immunization is a government program that aims to improve public health. The infant mortality rate in Indonesia is still very high. It is estimated that 1.7 million children or 5% of under-five deaths in Indonesia are due to diseases that can be prevented by immunization/PD3I. The quality of immunization services that are less than optimal will certainly waste the resources that have been spent, such as operational costs, vaccines, logistics, manpower, and time. Even the most concerning for all of us is the failure of immunization will threaten the occurrence of morbidity, disability, or death in children. This study aims to examine the relationship between basic immunization services and infant mother satisfaction at the Deleng Pokhisen Health Center in Southeast Aceh District in 2018.This type of research is a descriptive corelative study that explores how and why health phenomena occur with a cross sectional approach. The population is mothers who have babies aged 0-12 months. The sampling technique in this study was simple random sampling with a total of 64 people. The data analysis technique uses the chi square statistical test . The results obtained in this study are that there is a relationship between basic immunization services (tangibles, reliability, responsiveness, assurance, four) with the satisfaction of the baby's mother. there is a relationship between basic immunization services and infant mother satisfaction at the Deleng Pokhisen Health Center in Southeast Aceh District. Suggestions for Deleng Pokhisen Care, Southeast Aceh District, to maintain and maintain the quality of basic immunization services so that they continue to bring their babies back for immunization.